2021
DOI: 10.3389/fphar.2021.761814
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of UDP-Glucuronosyltransferases to Human Hepatic and Intestinal Metabolism of Ticagrelor and Inhibition of UGTs and Cytochrome P450 Enzymes by Ticagrelor and its Glucuronidated Metabolite

Abstract: Ticagrelor is the first reversibly binding, direct-acting, oral P2Y12 receptor inhibitor. The contribution of UDP-glucuronosyltransferases (UGTs) enzymes to the metabolism of ticagrelor to its glucuronide conjugation, ticagrelor-O-glucuronide, in human liver microsomes (HLM) and human intestinal microsomes (HIM), was well characterized in the current study. The inhibition potential of human major UGTs by ticagrelor and ticagrelor-O-glucuronide was explored. The inhibitory effects of ticagrelor-O-glucuronide on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Furthermore, our findings suggest that N -hydap downregulated the enzymatic activity of most DMEs in the liver, while it was interesting that the activity of several enzymes in the kidneys tended to be either opposite or unchanged. Literature reports suggest that drug metabolites can inhibit CYPs and UGTs [ 30 ]. Enzyme kinetic analysis of N -hydap glucuronidation revealed that liver microsomes exhibited a stronger affinity for N -hydap (lower K m value) and a faster conversion rate of N -hydap to N -hydap-G (higher CL int value) compared to renal microsomes in humans, rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings suggest that N -hydap downregulated the enzymatic activity of most DMEs in the liver, while it was interesting that the activity of several enzymes in the kidneys tended to be either opposite or unchanged. Literature reports suggest that drug metabolites can inhibit CYPs and UGTs [ 30 ]. Enzyme kinetic analysis of N -hydap glucuronidation revealed that liver microsomes exhibited a stronger affinity for N -hydap (lower K m value) and a faster conversion rate of N -hydap to N -hydap-G (higher CL int value) compared to renal microsomes in humans, rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…This low bioavailability is the result of intestinal metabolism primarily driven by UGT1A9 and UGT1A10, leading to a pronounced intestinal first-pass effect (Mizuma, 2009;Ritter, 2007). Another example is ticagrelor, for which in vitro studies in human intestinal microsomes indicated a glucuronidation activity and additional evaluation in recombinant system confirmed the implication of UGT1A9 (main) and UGT1A7, UGT1A3, UGT1A4, UGT1A1, UGT2B7 and UGT1A8 as enzymes involved in its metabolism (Liu et al, 2021).…”
Section: Table 9)mentioning
confidence: 99%
“…Ticagrelor undergoes oxidation primarily via CYP3A4, and to a lesser extent CYP3A5, to produce an active metabolite (AR-C124910XX [also known as M8]), which has concentrations that are about one-third of the parent drug with equivalent potency. [13][14][15][16]…”
Section: Prasugrel and Ticagrelormentioning
confidence: 99%
“…Ticagrelor is a substrate for both P‐gp in the intestine and the solute carrier organic anion transporter family member 1B1 (SLCO1B1) in the liver and undergoes glucuronidation via multiple UDP‐glucuronosyltransferase (UGT) isoforms (e.g., UGT1A9, UGT1A7, and UGT2B7) to form a glucuronide conjugate. Ticagrelor undergoes oxidation primarily via CYP3A4, and to a lesser extent CYP3A5, to produce an active metabolite (AR‐C124910XX [also known as M8]), which has concentrations that are about one‐third of the parent drug with equivalent potency 13‐16 …”
Section: Pharmacology Of Oral P2y12 Receptor Inhibitorsmentioning
confidence: 99%